The The Effectiveness of Virtual Reality in Mathematics for SPLDV Material - Komang Elik Mahayani; Ketut Agustini; I Gde Wawan Sudatha (Journal of Education Technology, 2023)
The lack of learning media and teacher creativity in implementing mathematics learning results in a lack of students' understanding and enthusiasm in learning mathematics. This research aims to analyze the design, feasibility, effectiveness and response of teachers and students in implementing virtual reality learning based on case-based learning in class VIII mathematics subjects. The research uses the Dick and Carey development model. The research subjects consisted of two content experts, one instructional design expert, one learning media expert, three individual test students, nine small group test students, and thirty-two field test students. The data collection methods used were interviews, questionnaires, tests and documentation. The data analysis techniques used are quantitative descriptive analysis, inferential statistical analysis (t-test), and N-Gain test. The content expert test results showed very high validity based on Gregory's validity. The expert test found, the score percentage is considered very good. Based on the t-test calculation, the significance value (Sig. 2-tailed) of 0.000 is smaller than 0.05 (p > 0.05), rejecting the null hypothesis (H0) and accepting the alternative hypothesis (Ha). So, it can be concluded that there is a significant difference in learning outcomes before and after using virtual reality based on case-based learning. The N-Gain calculation produces a score of 0.741, which indicates a high category so it can be concluded that the use of virtual reality learning based on case-based learning is effective in improving student learning outcomes in class VIII mathematics subjects.